Pengaruh Ketidakamanan Kerja, Komitmen Organisasional dan Kepercayaan Organisasional pada Keinginan Berpindah - fadzilah, abdulllah al; Martono, S (Management Analysis Journal, 2016)
The purpose of this study is to examine the effects of job insecurity, organizational commitment, and organizational trust on turnover intentions. The samples that were used in this study were 104 employees obtained by using the Slovin’s formula. The data were collected by using questionnaire method. The data analysis usespercentage descriptive analysis, and partial regression analysis uses SPSS for Windows version 16. The results of this study show that job insecurity influences turnover intentionspositively and significantly, while the organizational commitment and organizational trust influencenegatively and significantly. The study concluded that the higher job insecurity is, the higher turnover intentionswill be, and the higher commitment and organizational trust are, the lower turnover intentions will be. The suggestions from this study are to minimize job insecurity and turnover intentions and to increase the commitment and organizational trust, such as bythe availability of employee briefing-and-sharing with the leader, giving punishments if the employee resigns before the specified time period and giving rewards for employees with achievements.